Structural and Functional Characterization of Hermetia illucens Larval Midgut - Bonelli, Marco; Bruno, Daniele; Caccia, Silvia; Sgambetterra, Giovanna; Cappellozza, Silvia; Jucker, Costanza; Tettamanti, Gianluca; Casartelli, Morena (Frontiers in Physiology, 2019)
The larvae of Hermetia illucens are among the most promising agents for the bioconversion of low- quality biomass, such as organic waste, into sustainable and nutritionally valuable proteins for the production of animal feed. Despite the great interest in this insect, the current literature provides information limited to the optimization of rearing methods for H. illucens larvae, with particular focus on their efficiency in transforming different types of waste and their nutritional composition in terms of suitability for feed production. Surprisingly, H. illucens biology has been negleted and a deep understanding of the morphofunctional properties of the larval midgut, the key organ that determines the extraordinary dietary plasticity of this insect, has been completely overlooked. The present study aims to fill this gap of knowledge. Our results demonstrate that the larval midgut is composed of distinct anatomical regions with different luminal pH and specific morphofunctional features. The midgut epithelium is formed by different cell types that are involved in nutrient digestion and absorption, acidification of the lumen of the middle region, endocrine regulation, and growth of the epithelium. A detailed characterization of the activity of enzymes involved in nutrient digestion and their mRNA expression levels reveals that protein, carbohydrate and lipid digestion is associated to specific regions of this organ. Moreover, a significant lysozyme activity in the lumen of the anterior and middle regions of the midgut was detected. This enzyme, together with the strong acidic luminal pH of middle tract, may play an important role in killing pathogenic microorganisms ingested with the feeding substrate. The evidence collected led us to propose a detailed functional model of the larval midgut of H. illucens in which each region is characterized by peculiar features to accomplish specific functions. This platform of knowledge sets the stage for developing rearing protocols to optimize the bioconversion ability of this insect and its biotechnological applications.